Detecting malingered memory problems in the civil and criminal arena - Van Oorsouw, Kim; Merckelbach, Harald (Legal and criminological psychology, 2010)
Feigning a psychiatric or neurological disorder may be an attractive strategy to obtain all sorts of privileges or disability benefits. In the criminal arena, feigning memory loss for a crime (crime‐related amnesia) may be a way for defendants to gain sympathy or to promote a diminished capacity defence. Although crime‐related amnesia may, under some circumstances, be genuine, in many cases it is more likely to be malingered. Malingered memory problems are a subtle form of deception and what is true for deceptive behaviour in general is also true for malingering memory loss: on the basis of clinical intuition alone, it is difficult to detect. Fortunately, there are methods and tools to evaluate the authenticity of memory problems. It is important that forensic and clinical psychologists familiarize themselves with these techniques.